Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper investigates skills mismatch and active labor market policy in Lithuania. Wage flexibility is underpinned by one of the lowest densities of trade union and employer organization and the rare occurrence of collective bargaining. Thus, wage setting largely happens at the firm level. Real wages and productivity have been traditionally closely linked and temporary deviations have been self-correcting. In contrast, structural unemployment has been traditionally high, although it appears to be gradually falling. Large structural unemployment can have a significant long-term impact on potential growth and, therefore, on employment. Lithuania suffers from relative labor shortage for high-skilled workers and surplus of low- and medium-skilled workers. Thus, there are labor shortages in skill-intensive sectors. Lithuania has shown a sharp rise in skills mismatch for the country in the aftermath of the crisis. Vacancy rates and wage growth by sectors also suggest an excess supply of lower skilled workers and shortage of high-skilled ones.